O11.5. EXPLORING SPECIFIC EFFECTS OF TYPE AND TIMING OF EXPOSURE TO CHILDHOOD ADVERSITY AND SYMPTOM DOMAINS IN FIRST EPISODE OF PSYCHOSIS: PRELIMINARY RESULTS FROM THE EUGEI PROJECT. (9th April 2019) - Alameda, Luis; Rodriguez, Victoria; Gayer-Anderson, Charlotte; Aas, Monica; Quattrone, Diego; Tripoli, Giada; Wong, Chloe; Forti, Marta Di; Morgan, Craig; Murray, Robin
Abstract: Background: While it is generally accepted that childhood adversity (CA), mainly in the form of abuse and neglect is associated with psychosis, less attention has been paid to the specific effects of different adversity types and symptoms in patients. Concretely, the association between specific adversity types and the main symptom dimensions in First Episode of Psychosis (FEP), considering the timing of exposure has never been studied. This is the aim of the current investigation. Methods: 1130 FEP patients were recruited as part of the EUGEI multicentric case-control study. The Childhood Experience of Care and Abuse Questionnaire (CECA.Q) was used to investigate the experiences of abuse (sexual, physical and psychological), household discord, neglect, bullying, parental separation and parental death prior the age of 17. Each adversity was categorized according to the time of exposure as follows (Early: before 12 years of age; Late: from 12 through 17). Symptom dimensions (positive, negative, disorganised, manic and depressive) were built from the OPerational CRITeria (OPCRIT) using Mplus. Linear regression was used to examine associations between each type of CA and the continuous symptom dimension scores. Results were controlled for age, sex, ethnicity, site and years of education. Results: Early-sexual abuse [B = 0.417, 95% confidence interval (CI) 0.059–0.775], Late-neglect (B = 0.473, 95% CI 0.072–0.874] and Late-parental death [B = 0.547, 95% CI 0.219–0.876] showed a significant association with the positive symptom dimension; Late-bullying (B = 0.249, 95% CI 0.056–0.443] was significantly associated with the depressive dimension and Early-neglect (B = 0.249, 95% CI 0.011–0.487] with the manic dimension. Discussion: Our results provide evidence for some specificity effects between different adversities and the positive, depressive and manic dimensions in FEP. In addition, the time at which such adversities occur seems to play role in such associations. The exploration of psychological and biological underlying mechanisms explaining such links is warranted.